Guides for value chain development: A comparative review - Donovan, Jason; Franzel, Steven; Cunha, Marcelo; Gyau, Amos; Mithofer, Dagmar (Emerald Publishing Limited, 2015)
– In recent years, governments, donors, and NGOs have increasingly embraced value chain development (VCD) for stimulating economic growth and combating rural poverty. In line with the rise in interest, there has been a proliferation of guides for VCD. The purpose of this paper is to present the results of a review of 11 guides for value chain along six different dimensions, ranging from objectives and value chain definitions to monitoring impact. The paper concludes with suggestions for the use of guides based on local needs and context, and recommendations for future guide development.– The review compares the concepts and methods endorsed and it assesses the strengths and limitations of the guides for steering development practice.– Overall, the guides provide a useful framework for understanding markets and engaging with chain stakeholders, with a strong emphasis on strengthening institutions and achieving sustainability of interventions. However, the guides often lack discussions on the conditions necessary at different levels for VCD to advance development objectives and achieve that sustainability. The guides are designed to be implemented largely independently of the specific context, in which the chain is situated, despite the major implications context has for the design of interventions and overall success of the chain. Attention to mutual learning, whether related to tool design or the outcomes and impacts of VCD interventions, is limited.– More critical reflection and debate is needed on the design of guides for VCD. The authors suggest three areas for this reflection and debate: concepts, methods, and tools for addressing the needs of the poor in value chains; tools for addressing variations in the context; and mechanisms for mutual learning on the design and implementation of VCD.– The paper concludes with various recommendations for guide authors and donors that support VCD.